P96. Intrathecal immunglobulin synthesis: Sensitivity of kappa free light chains in cerebrospinal fluid to identify patients with oligoclonal bands. Issue 8 (August 2018) - Süße, M.; Hannich, M.; Petersmann, A.; Zylla, S.; Pietzner, M.; Nauck, M.; Dressel, A.
Abstract : Objective: Intrathecal immunoglobulin synthesis can be present in inflammatory diseases of the central nervous system. The gold standard with highest sensitivity for intrathecal immunglobulin G synthesis is the measurement of oligoclonal bands (OCB). There is rising evidence that the determination of a kappa free light chains (KFLC) index has a similar sensitivity in the diagnostics of diseases associated with detection of OCB in CSF. While detection of OCB is time consuming and the qualitative result relies on experienced evaluators, KFLC measurement is a quantitative method that can be rapidly performed in a highly automated setting. In the present prospective study, we aimed to determine a nonselective optimal cut-off value for determination of the KFLC index in routine clinical CSF analysis. Methods: 300 consecutive routine serum and CSF samples were measured on the Siemens BN Prospec using the Siemens N Latex FLC kappa Kit on the BN Prospec. We evaluated the diagnostic performance of KFLC for the prediction of OCB in CSF by quantile regression and ROC analysis. The assessed reference limits were prospectively validated in 100 consecutive samples as well as retrospectively in 50 OCB positive paired patient samples. Results: Using quantile regression for establishing the 95% percentile of KFLC quotient in relation to Albumin quotient in OCB negative patients ( n  = 266) revealed a sensitivity of 88% and a specificity of 95%. The optimal cut-off value for KFLC index for OCB detection using ROC analysis was 4.93 with a sensitivity of 94% and a specificity of 91%. After extrapolation for highest sensitivity to prevent false negative results the cut-off value for KFLC index was 3.56. Validation of this value prospectively in a second cohort of 100 patient samples revealed 88% sensitivity and 93% specificity. Testing this value retrospectively in 50 OCB positive patients revealed 94% sensitivity. Discussion: The KFLC index cut-off value 3.56 has a high diagnostic accuracy for detecting intrathecal immunglobulin G synthesis in comparison with OCB. We conclude that KFLC index determination is suitable for a complementary diagnostic step before applying OCB detection as control and as qualitative evaluation of intrathecal immunglobulin G synthesis. By using automated KFLC tests laboratory work flow is optimized. Multi center studies and comparison of different methods are required to confirm the results of this monocentric study.